Methodological basis of the development management of small businesses in housing and utilities infrastructure - Solodova E. P. (Interactive science, 2017)
the article analyzes the mainstreaming of necessary distinction between «growth» and «development» definitions, applied to the process of development management of small enterprises. There is the author's interpretation of the concept of «small businesses in housing and utilities infrastructure». The management model was designed for the development management of small businesses in housing and utilities infrastructure.
Keywords: малые предприятия; жилищно-коммунальное хозяйство; управление развитием; малые предпринимательские структуры; small businesses; housing and utilities infrastructure; development management; small enterprises